UJI VALIDITAS INSTRUMEN B-IPQ VERSI INDONESIA PADA PASIEN HIPERTENSI DI RSUD SULTAN SYARIF MOHAMAD ALKADRIE PONTIANAK - Robiyanto, Robiyanto (Universitas 17 Agustus 1945 Jakarta, 2016)
Validity and reliability tests of Indonesian version of Brief-Illness Perception Questionnaire (B-IPQ) instrument are important to determine is this instrument valid and reliable in clasifying the patients’ perception toward the condition of disease they have. The purpose of this research is to measure the validity and reliability of Indonesian version of B-IPQ instrument which were given to 30 patients with hypertension treated at RSUD Sultan Syarif Mohamad Alkadrie Pontianak. This was an observational study with analytical survey method and cross-sectional approach. Validity test was measured using Pearson correlation (correlation score ≥ 0,3) and for reliability test using Internal consistency technique (Cronbach alpha coefficient ≥ 0,7). The result of validity test showed the correlation score in each item was > 0.3 (0.05) and the result of reliability test showed the Cronbach alpha coefficient was 0.807 > 0.7 (0.05). From these two tests results it can be concluded that the Indonesian version of B-IPQ instrument is valid and reliable in measuring the perception of hypertension patient at RSUD Sultan Syarif Mohamad Alkadrie Pontianak.